Propostas de algoritmos e fórmulas para planejamento cirúrgico dos estrabismos horizontais - Rocha, Maria Nice Araujo Moraes (2016)
The objective of this study was to propose the planning of surgery for correction of horizontal strabismus, esotropia and exotropias through algorithms and formulas that convert the measure of the deviation angle prism diopters to millimeters, which is used in surgical practice. Demonstrated the preparing of the formulas and flowcharts according to the theoretical foundations presented. Was make retrospective analysis of 136 patients operated in accordance with the algorithms and formulas proposed. Two algorithms were constructed on the basis of anatomy, physiology and oculomotricity, instrumental in planning and semiotics of strabismus surgery. The preparation of the formulations was done using mathematical calculations associated with knowledge of the mechanics of eye movements. It was completed two formulas for esotropias correction: ET1 and ET2 = = 0,33D 0,30D and two for exotropias correction: XT1 and XT2 = = 0,40D 0,43D, dependent on the number of eyes to be operated and magnitude of the deviation. For this work was adopted as individual success criteria to orthotropia ± 10Δ, in agreement with several studies in the literature. The result of successful group in the immediate post operative period (7days after surgery) was equal to 92.9% in the correction of esotropia and 82.3% in exotropias. In the late postoperative period (3-6 months after surgery) there was the result of success were 75.3% and 62.8% for esotropias to exotropias. The results were compared to studies conducted in similar conditions and concluded that the proposed method is effective for surgical planning in correcting esotropias and exotropias.